Transcriptome and metabolome analyses reveal the key genes related to grain size of big grain mutant in Tartary Buckwheat (Fagopyrum tartaricum) - Fang, Xiaomei; Wang, Yingqian; Cui, Jingbin; Yue, Linqing; Jiang, Aohua; Liu, Jiaqi; Wu, Yichao; He, Xingxing; Li, Chunhua; Zhang, Jian; Ding, Mengqi; Yi, Zelin (Frontiers in Plant Science, 2022)
Grain size with high heritability and stability is an important selection target during Tartary buckwheat breeding. However, the mechanisms that regulate Tartary buckwheat seed development are unknown. we generated transcriptome and metabolome sequencing from developing grains of big grain mutant bg1 and WT at 10 and 15 DPA, and identified 4108 DEGs including 93 significantly up-regulated differential genes and 85 significantly down-regulated genes in both stages, simultaneously. Meanwhile, we identified DEGs involved in ubiquitin-proteasome pathway, IKU pathway, MAPK signaling pathway, plant hormone (auxin, BR and CTK) transduction pathway and five TF families (AP2, GRF, ARF, WRKY and MYB). WGCNA was performed and obtained 9 core DEGs. Conjoint analyses of transcriptome and metabolome sequencing screened out 58 DEGs. Using a combined comprehensive analysis, we identified 24 potential candidate genes that encode E3 ubiquitin-protein ligase HIP1, EMB, receptor-like protein kinase FERONIA FER, SRG1, which may be associated with the big-grain mutant bg1. Our results provide additional knowledge for identification and functions of causal candidate genes responsible for the variation in grain size and will be an invaluable resource for the genetic dissection of Tartary buckwheat high-yield molecular breeding.